Sleep disorders and it,s risk factors in nurses - E Razmpa; M Ghaffarpour; KH Sadeghniiat Haghighi; HA Ghelichnia; M Ghobaei; NA Rezaei; KH Davari; A Asadi (طب کار)
Abstract Background: There are many risk factors that predispose nurses to sleep disorders. In one hand, sleep disorder affects health and safety of nurses and patients and on the other hand, risk factors of this occupations raise the prevalance of sleep disorders and their complications. Materials and Methods: this study was done cross-sectionally on 190 nurses of Imam Khomeini hospital in Tehran, Iran. We used sleep impairment index for insomnia, Epworth sleepiness scale for excessive daytime sleepiness, Martinez method for obstructive sleep apnea syndrome, and sleep disorder was defined as insomnia or hypersomnolance. Results: prevalence of sleep disorders, insomnia, excessive daytime sleepiness, obstructive sleep apnea syndrome, and narcolepsy was, 83.8%, 81.5%, 33.1%, 12.1%, 3.7%, respectively. Using multivariable model, just shift work was significantly effective on prevalence of sleep disorders. Conclusion: We determined the prevalence of important subtypes of sleep disorders in nurses by standard self-report questionnaires and physical exam. Many risk factors that other studies in western countries have shown their importance, can't affect the prevalence of sleep disorders in Iranian nurses. To find the true reason for this issue, we suggest that a study must be done to compare occupation definition, Job, and task of Iranian nurses with western nurses.